a, \(A=x^2\left(2x-1\right)+x\left(x+8\right)=2x^3-x^2+x^2+8x=2x^3+8x\)
Thay x = -2, ta có:
\(2\cdot\left(-2\right)^3+8\cdot\left(-2\right)=-32\)
b, \(A=2x^3+8x=0\\ \Leftrightarrow2x\left(x^2+4\right)=0\\ \Leftrightarrow x=0\)
Vậy A=0 khi x=0
a,A = \(x^2\).( 2\(x\) - 1) + \(x\)(\(x+8\))
A = 2\(x^3\) - \(x^2\) + \(x^2\) + 8\(x\)
A = 2\(x^3\) + 8\(x\)
b, \(x=-2\) ⇒ A = 2.(-2)3 + 8.(-2) = - 32
A = 0 ⇔ 2\(x^3\) + 8\(x\) = 0
2\(x\left(x^2+4\right)\) = 0
vì \(x^2\) + 4 > 0 ∀ \(x\) ⇒ \(x\) =0
\(a,A=x^2\left(2x-1\right)+x\left(x+8\right)\\ =2x^3-x^2+x^2+8x=2x^3+8x\\ =2x.\left(x^2+8\right)\\ Thế.x=-2.vào.A:A=2x.\left(x^2+8\right)=2.\left(-2\right).\left[\left(-2\right)^2+8\right]=-4.12=-48\\ b,A=0\\ \Leftrightarrow2x\left(x^2+8\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x^2+8=0\left(vô.lí\right)\end{matrix}\right.\Leftrightarrow x=0\\ Vậy:A=0\Leftrightarrow x=0\)
...................... =) A = 0 khi x = 0.